2009
DOI: 10.1073/pnas.0903609106
|View full text |Cite|
|
Sign up to set email alerts
|

SPLUNC1 regulates airway surface liquid volume by protecting ENaC from proteolytic cleavage

Abstract: Many epithelia, including the superficial epithelia of the airways, are thought to secrete “volume sensors,” which regulate the volume of the mucosal lining fluid. The epithelial Na + channel (ENaC) is often the rate limiting factor in fluid absorption, and must be cleaved by extracellular and/or intracellular proteases before it can conduct Na + and absorb excess mucosal liquid, a process that can be blocked by proteases inhibitors. In the airways, airway surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
185
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(191 citation statements)
references
References 46 publications
6
185
0
Order By: Relevance
“…The mouse and human BPIFA1 sequences are homologous 8, 10, 11 . 7 Previous studies have demonstrated that BPIFA1 acts as a surfactant 12 , can 8 regulate the amiloride-sensitive epithelial sodium channel, ENaC 13 and affects 9 mucociliary clearance in the upper airways 14 . It has also been shown to have anti-10 bacterial roles.…”
mentioning
confidence: 99%
“…The mouse and human BPIFA1 sequences are homologous 8, 10, 11 . 7 Previous studies have demonstrated that BPIFA1 acts as a surfactant 12 , can 8 regulate the amiloride-sensitive epithelial sodium channel, ENaC 13 and affects 9 mucociliary clearance in the upper airways 14 . It has also been shown to have anti-10 bacterial roles.…”
mentioning
confidence: 99%
“…In addition to its potential antimi-crobial function, SPLUNC1 regulates airway surface liquid volume in vitro. 7 Each year, approximately 2 million pneumonia cases due to infection with Mycoplasma pneumoniae (Mp), including 100,000 hospitalizations, are reported in the United States. 8 Mp is an atypical bacterium that lacks a cell wall and relies on adhesion to host cells for colonization and infection, which is generally restricted to airway epithelium.…”
mentioning
confidence: 99%
“…(17) SPLUNC1 has also been shown to have an anti-inflammatory function in exogenous microbe-induced respiratory infection, such as K. pneumoniae, (18) Mycoplasma pneumoniae, (19) P. aeruginosa, and Epstein-Barr virus. (20) Additionally, SPLUNC1 could also regulate ion/mucus transport and hydration levels in the lung, (21) lower surface tension by its surfactant-like properties, (22) and act as an inflammatory mediator.…”
Section: Discussionmentioning
confidence: 99%